1999
DOI: 10.1046/j.1365-2168.1999.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic role for nitric oxide in experimental renal warm ischaemia–reperfusion injury

Abstract: Inhibition of the postischaemic increase in the level of nitric oxide was associated with an early decrease in, but eventual exacerbation of, oxidative damage. This suggests the prolonged increase in renal nitric oxide concentration was cytoprotective overall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 41 publications
2
17
0
1
Order By: Relevance
“…2,39,[41][42][43] Reactive oxygen and nitrogen species are believed to play a central role in I/R injury in addition to several other factors, such as neutrophils, platelets, the coagulation system and the xanthine-oxidoreductase enzyme system. Our previous report demonstrated that renal I/R worsened the renal dysfunction, oxidative stress and histopathologic features in rats.…”
Section: Discussionmentioning
confidence: 99%
“…2,39,[41][42][43] Reactive oxygen and nitrogen species are believed to play a central role in I/R injury in addition to several other factors, such as neutrophils, platelets, the coagulation system and the xanthine-oxidoreductase enzyme system. Our previous report demonstrated that renal I/R worsened the renal dysfunction, oxidative stress and histopathologic features in rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been demonstrated that NO plays a biphasic role in pathophysiology of renal injury mediated by I/R [30]. In early phases, the increased oxidative and nitrosative damage was exacerbated by NO donors but ameliorated by NOS inhibition [5,30].…”
Section: Discussionmentioning
confidence: 99%
“…They further alleged that NOS played a cytotoxic role in the early stages while it had a cytoprotective role in the late stages. Other researchers have also examined the biphasic effect of NO [9,10] .…”
Section: Discussionmentioning
confidence: 99%